Little Red Riding Hood - Moore, Maggie and Knight, Paula (Franklin Watts Ltd, 2001)
Little Red Riding Hood sets off through the forest to visit her grandmother, who is ill. On the way, she meets a big, bad wolf. But watch out, the wolf has a sneaky plan!
Keywords: Anthologies; Fairy Tales & Folklore; Juvenile Fiction